Emotional Creativity as Predictor of Intrinsic Motivation and Academic Engagement in University Students: The Mediating Role of Positive Emotions - Oriol, Xavier; Amutio, Alberto; Mendoza, Michelle; Da Costa, Silvia; Miranda, Rafael (Frontiers in Psychology, 2016)
Objective: Emotional creativity implies experiencing a complex emotional life, which is becoming increasingly necessary in societies that demand innovation and constant changes. This research studies the relation of emotional creativity as a dispositional trait with intrinsic motivation and academic engagement. Methods: A sample of 428 university Chilean students, 36.5% men and 63.5% women, with ages from 18 to 45 years old (M = 20,37 DT = 2,71). Additionally, the mediating function of class-related positive emotions in this relation is explored. Results: The obtained data indicate that developing high levels of dispositional emotional creativity enhances the activation of positive emotions, such as gratitude, love and hope, in the classroom. Furthermore, emotional creativity predicts intrinsic motivation and academic engagement of university students by the experience of positive emotions. Conclusion: These results compel us to be aware of the importance that university students in their early years can understand the complexity of the emotional processes they undergo. A greater control of these emotions would allow students to maintain higher levels of interest in their studies at the different educational stages and to avoid the risk of school failure.